Oral Sex in the Perspective of Islamic Law - Muhammad Khusna Syah; Hudallah (Ushul Al-Hukm: Jurnal Syariah dan Hukum Islam, 2025)
The issue of oral sex has caused many scholars in various Muslim countries to be interested in analyzing and issuing fatwas. The majority of these ulama's fatwas are ethical in nature. This means that the issue of oral sex is still resolved at the level of assumptions only and has not touched on substantial reasons. This is understandable because the issue of oral sex is a taboo subject to discuss. Apart from that, this issue also invites conflict of opinion among scholars because there is no definite religious text explaining this matter. Therefore there is disagreement. Oral sexual activity carried out by husband and wife couples is a social phenomenon that can be said to be new among Indonesian society, even in Islamic discourse. This has given rise to debate among Muslim scholars about the permissibility of carrying out this activity. However, most scholars allow oral sexual activities, including Shahid Athar, a scholar and expert in Islamic sexology. However, there are quite a few who forbid this activity. One of them is Sheikh an-Najmi, a mufti of southern Saudi Arabia.